Toward Controlling the Formation, Degradation Behavior, and Properties of Hydrogels Synthesized by Aza‐Michael Reactions. Issue 16 (11th July 2013) - Southan, Alexander; Mateescu, Markus; Hagel, Valentin; Bach, Monika; Schuh, Christian; Kleinhans, Claudia; Kluger, Petra J.; Tussetschläger, Stefan; Nuss, Isabell; Haraszti, Tamás; Wegner, Seraphine V.; Spatz, Joachim P.; et al.
Abstract The aza‐Michael reaction of amino‐functionalized polymers with acrylate and acrylamide crosslinkers for the formation of hydrogels is investigated. It is studied how far the reaction conditions (pH value, chemical structures of the compounds involved) influence the crosslinking and degradation rate of the gels. When crosslinking the polymer poly(1‐glycidylpiperazine), high pH values lead to fast crosslinking. Fast degradation of β‐aminoester crosslinks is observed when acrylate crosslinkers are used due to a neighboring group effect. With acrylamide crosslinkers, hydrolytically stable gels are formed, in which the shear moduli and swelling ratio can be adjusted and in which the extracts show no toxic effect on primary human fibroblasts, making them a promising material for biotechnological applications.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>